The e-commerce region of Helsingborg: : a report on the Helsingborg region's role in Swedish e-commerce - Deppert, Karsten; Johansson, Felicia (E-commerce Park, 2025)
Helsingborg has a strong trading heritage and a unique strategic location within the Nordic region. It's no coincidence that these factors have combined in the digital age to position Helsingborg as a key player in the world of e-commerce. The city's natural geographic advantages, alongside significant investments in infrastructure, have established a strong foundation for Helsingborg to become a leading e-commerce hub. Furthermore, Helsingborg offers several educational programs and research initiatives focused on e-commerce, clearly demonstrating that this sector plays a crucial role in the city's economy — both today and looking ahead. Helsingborg is not just a city with a strategic logistical advantage, but also one with a deep-rooted tradition of trade and entrepreneurship, an internationally recognized university, and an expanding tech sector. All of this while being a desirable place to live and part of the dynamic Öresund region. Together, these factors create an ideal environment for growth. This report aims to offer insights into the true strength of Helsingborg regions e-commerce sector.